The Effect of the Missouri Mathematics Project (MMP) Learning Model on Students' Mathematical Problem Solving Ability in Algebra Material in Class VII Budi Murni 2 Catholic Private Middle School Medan - Sella Eurora Bangun; W. L. Sihombing (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
This study aims to determine the significant effect of the Missouri Mathematics Project (MMP) learning model on students' mathematical problem solving abilities in algebraic material in class VII Budi Murni 2 Catholic Private Middle School Medan and how big the influence is. The population of the study were all students of class VII at Budi Murni 2 Catholic Private Middle School Medan, totaling 7 classes. Of the 7 classes, only one class will be used as an experimental class, namely class VII-6 with a total of 30 students using a purposive non-probability sampling technique. This type of research is experimental research, using Pre-Experimental Design. The research instrument used was a test, namely pre-test and post-test. Data analysis in this study used the help of the Statistical Package for the Social Sciences (SPSS) 22 program. From the results of the study it was found that in the experimental class the average pre-test score was 71.00 and the post-test average score was 85.80 . So it can be concluded that there is a significant influence of the Missouri Mathematics Project (MMP) learning model on students' mathematical problem solving abilities.